Low back pain : a personal projects analysis : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Psychology at Massey University, Palmerston North, New Zealand - Vroman, Kerryellen Griffith (Massey University, 2004)
Low back pain is characterised by loss of ability to carry out everyday tasks, the disruption of life plans, and psychological distress as well as pain. This study examined the adaptation of individuals with low back pain. In a departure from established models used to study and understand illness representation and adjustment, this study used a personal projects approach to examine the relationship between individuals' appraisals of projects and their functional adaptation to low back pain in the context of their day-to-day goal-directed activities. A functional personal project system was proposed; specifically, those individuals whose project dispositions were highly concordant and socially oriented would have better function and health. For people dealing with low back pain, it was expected that these dispositions, and personal competency, would enhance adaptation. Conversely, poor adaptive abilities, such as difficulties with physical function, social function, and poorer health, would be associated condition-specific perceptions of pain and negative appraisals of project stress[.] The results showed there was a relationship between personal project dispositions and functional ability, well-being, and perceived general health of individuals with low back pain. The results did not confirm that a functional project system possessed adaptive benefits. However, the appraisal of pain as salient to the progress and success of projects and stressfulness of personal projects were predictive of limited function and poorer health. Notably, all aspects of function, both social and physical, were associated with pain-salience cognition. Furthermore, pain salience cognition was still predictive of function after traditional predictors of low back pain disability, pain severity or pain-related fear, were included in the analysis. The significance of the relationship of pain and negative appraisals of the effect of pain on performance supports functional self-efficacy and pain-related fears models used to explain disability level in individuals with low back pain. Since this personal projects analysis was an integrated assessment of individuals' dispositions in the context of participants' everyday lives, it was concluded that pain salience and stressfulness of projects outweighed any advantages offered by their other dispositions in negotiating the participant's personal projects.
Keywords: Lower back pain; Psychological effect of pain; Fields of Research::380000 Behavioural and Cognitive Sciences::380100 Psychology::380107 Health, clinical and counselling psychology